PERCEPATAN PERTUMBUHAN BENIH KERANG MUTIARA (Pinctada maxima) MENGGUNAKAN METODA PERENDAMAN DALAM BAK PAKAN ALAMI - Alis Mukhlis; Nadirah Karimatul Ilmi; Sanca Rahmatullah; Anita Prihatini Ilyas; Awan Dermawan (Jurnal Perikanan Unram, 2021)
Pearl oyster (Pinctada maxima) is one of the marine resources that has high economic value but its production takes a long time, so it takes a long time to be marketed. The imbalance between feed requirements and the availability of natural food in the waters is thought to be one of the factors for the slow growth of pearl oyster seeds. This problem can be overcome by immersing it in natural feed tanks periodically so that the need for pearl oyster seed feed can be met. The purpose of this study was to determine the effect of the immersion period of seeds in natural feed tanks on the growth of pearl oyster seeds. This research was conducted in June – September 2019 in Teluk Siung, Batu Putih Village, West Sekotong District, West Lombok Regency, West Nusa Tenggara. The design used was a completely randomized design consisting of five treatments, namely A, without immersion (as a control); B, immersion at intervals of 1 week; C, soaking at intervals of 2 weeks; D, immersion at intervals of 3 weeks; and E, immersion at 4-week intervals. The results showed that immersion in natural feed tanks had a significant effect on the growth of the shell (dorso-ventral) of Pinctada maxima pearl shells (p<0.05). The highest growth was achieved in immersion with time intervals every 2 weeks with an absolute growth value of 10.99 mm, a specific growth of 219.8% of the initial size, and a specific growth rate of 1.30% per day. This method needs to be tested on seeds that are larger than those used in this study to see the consistency of the application of the immersion method in the cultivation of pearl oyster seeds.